2007
DOI: 10.1086/518084
|View full text |Cite
|
Sign up to set email alerts
|

SwiftX‐Ray Observations of Classical Novae

Abstract: The new-ray burst (GRB) mission Swift has obtained pointed observations of several classical novae in outburst. We analyzed all the observations of classical novae from the Swift archive up to 2006 June 30. We analyzed usable observations of 12 classical novae and found 4 nondetections, 3 weak sources, and 5 strong sources. This includes detections of two novae exhibiting spectra resembling those of supersoft X-ray binary source spectra (SSS), implying ongoing nuclear burning on the white dwarf surface. With t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 30 publications
3
90
0
Order By: Relevance
“…Ness et al 2007a;Orio et al 2001) are similar to those of optical surveys. In our galaxy, the investigation of the whole nova population is hampered by the large area (namely the whole sky) to be scrutinised and by our unfavourable position close to the Galactic Plane.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ness et al 2007a;Orio et al 2001) are similar to those of optical surveys. In our galaxy, the investigation of the whole nova population is hampered by the large area (namely the whole sky) to be scrutinised and by our unfavourable position close to the Galactic Plane.…”
Section: Introductionsupporting
confidence: 82%
“…In our galaxy, the investigation of the whole nova population is hampered by the large area (namely the whole sky) to be scrutinised and by our unfavourable position close to the Galactic Plane. As Ness et al (2007a) pointed out, the detectability of a SSS is highly dependent on its foreground absorption, which is affecting the supersoft X-rays much stronger than harder photons. Note that Orio et al (2001) analysed 350 archival ROSAT observations and found SSS emission for only three Galactic novae.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral model consists of a soft and a hard component, so the 2Y10 keV luminosity should be somewhat lower. The remainder of classical novae are taken from the Swift survey of classical novae ( Ness et al 2007). As the focus of this paper is the supersoft component, they do not provide luminosities or the conversion factor appropriate for the shell X-rays.…”
Section: Novae As X-ray Transientsmentioning
confidence: 99%
“…X-ray telescope (XRT) data were extracted and processed using the standard Swift tools 24 , specifically xrtpipeline v0.11.3. We used event grades 0-12 and extracted events using a 24 arcsec radius region around the nova (Ness et al 2007). Table 2 for line identifications in the 0.8-4.5 μm region).…”
Section: Observationsmentioning
confidence: 99%
“…In Table 4 we list the observation day, exposure time, count rate, and hardness ratio. The count rates were obtained as described in the Appendix in Ness et al (2007). We also extracted spectra from the recorded photon energies; however, the number of photons was insufficient to obtain a well exposed spectrum.…”
Section: Swift X-ray Telescope Observationsmentioning
confidence: 99%